Systematic Literature Review: Efektivitas Media Interaktif Dalam Pembelajaran Matematika - Tiara Pamula Wardani; Fitrianto Eko Subekti (Jurnal Ilmiah Wahana Pendidikan, 2022)
In various learning areas mathematics still held online . Implementation online learning requires a innovation both the strategy and the media used . Use of learning media expected capable increase results study participant educate . Study this aim for To do study literature about use of interactive media in learning math . Method research used is a Systematic Literature Review (SLR) with review article related to learning media there are interactive in Google Scholar using help Publish on Perish application . Articles used is published in period 5 years time last . Search results study literature give description that the interactive media used in learning mathematics could increase results study , think creative , and get response positive from participant educate . With thereby in teach math teacher always use and optimize learning media innovative .